PorA Variable Regions of Neisseria meningitidis - Russell, Joanne E. (Centers for Disease Control and Prevention, 2004)
Subtypes, defined by variation in the outer membrane protein PorA, are an integral part of the characterization scheme for Neisseria meningitidis. Identification of these variants remains important as the PorA protein is a major immunogenic component of several meningococcal vaccines under development, and characteristics of PorA are used to provide detailed epidemiologic information. Historically, serosubtypes have been defined by reactivity with a set of monoclonal antibodies. However, nucleotide sequence analyses of porA genes have established that the panel of serosubtyping monoclonal antibodies is not exhaustive and many porA variants cannot be detected. In addition, the nomenclature system used to define subtypes is inadequate. We examined all available nucleotide sequences of the porA VR1 and VR2 regions to identify and define subtype families. A revised nomenclature scheme, compatible with the previous serologic nomenclature scheme, was devised. A Web-accessible database describing this nomenclature and its relationship to previous schemes was established (available from: http://neisseria.org/nm/typing/pora).